Response rates to HB vaccine in CKD stages 3-4 and hemodialysis patients - Mohammad H Ghadiani; Shahin Besharati; Nouraddin Mousavinasab; Mojgan Jalalzadeh (Journal of Research in Medical Sciences, 2012)
Background: Hepatitis-B virus (HBV) infection is a big problem in chronic kidney disease (CKD) population. We attempted to compare the response rate to HB vaccine in CKD stages3-4 patients with that in hemodialysis (CKD stage-5; HD patients) and medical staff. Materials and Methods: Three hundred and three participants were enrolled into the study to test the seroconversion rate after vaccination. Participants formed three groups: Group-A:HD patients, Group-B: diagnosed with CKD stages 3-4, and Group-C: healthy medical staff. CKD stages 3-4 participants were vaccinated from February to November 2010. HD patients were vaccinated at the time of initial HD. While the medical staffs were vaccinated at the time they started working at the hospital. Group-A, Group-B and Group-C received four 40μg (in 0,1,2 and 6 months), three 40μg (0, 1 and 6 months) and three 20μg (0, 1and 6 months) doses of HB vaccine, respectively. Three months after completion of the vaccination schedule, seroconversion and seroprotection rates in each group were investigated. Results: Seroconversion rates were 44.3%, 89.7%, and 96.2% for groups A, B and C, respectively. CKD stages 3-4 patients showed higher response rate than dialysis patients [χ2 (1):30.6, P <0.001]. But a significant difference in the seroconversion rate between CKD stages 3-4 patients and medical staffs was not observed [χ2 (1):3.4, P = 0.064]. Multivariate analyses showed patients with more advanced CKD and who were older had less seroconversion rates [odds ratio: 0.09(95%CI: 0.04 - 0.25) and [odds ratio: 0.39(95% CI: 0.18-0.85)], respectively. But sex was not associated with seroconversion (P>0.05). Conclusion: Stages 3-4 patients with higher dosages of routine HB vaccine had higher seroconversion rate than HD patients. Future studies should evaluate the recommended dosage of HB vaccine among these patients.